2004
DOI: 10.1159/000082919
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum CA-15.3 Levels in Patients with Megaloblastic Anemia due to Vitamin B<sub>12</sub> Deficiency

Abstract: Objectives: To estimate the usefulness of serum tumor markers’ monitoring, as predictors of gastric cancer in patients with pernicious anemia. Patients and Methods: We investigated serum levels of carcinoembryonic antigen (CEA), α-fetal protein, cancer antigen (CA)-19.9, CA-125 and CA-15.3 in 50 patients with pernicious anemia and in 24 healthy controls, matched for age and sex. In 38 patients, the evaluation was repeated 1–6 months after the correction of cobalamin deficiency. Results: All patients and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…No previous studies have evaluated the usefulness of tumor markers in the differential diagnosis of advanced tumors. Tumor markers are not specific for malignancy, and slightly elevated levels are found in some benign diseases, mainly liver or renal disorders, as our results confirm [28][29][30][31][32][33]. Most tumor markers show only slightly elevated levels in benign disease, and it is easy to discriminate between benign and malignant disorders using a different cutoff (CEA, CA 15.3, CA 72.4, AFP, or NSE).…”
Section: Discussionsupporting
confidence: 57%
“…No previous studies have evaluated the usefulness of tumor markers in the differential diagnosis of advanced tumors. Tumor markers are not specific for malignancy, and slightly elevated levels are found in some benign diseases, mainly liver or renal disorders, as our results confirm [28][29][30][31][32][33]. Most tumor markers show only slightly elevated levels in benign disease, and it is easy to discriminate between benign and malignant disorders using a different cutoff (CEA, CA 15.3, CA 72.4, AFP, or NSE).…”
Section: Discussionsupporting
confidence: 57%
“…As a result of being retrospective, our study has revealed no information about the incidence of malignancy in ovarian cyst patients with high CA 125 levels or whether or not they underwent operations. This marker does not increase in megaloblastic anemia (Symeonidis et al, 2004). Literature does not confirm whether CA 125 levels are elevated or not in patients with other types of anemia.…”
Section: Discussionmentioning
confidence: 85%
“…In a previous study, the level of CA 19-9 was found to be elevated in 13 (3%) of patients with pneumonia (Marechal et al, 1988). It has been reported that in megaloblastic anemia the levels of CA 19-9 were not increased (Symeonidis et al, 2004). This marker was found to be sporadically high in patients with beta thalassemia (Christoforidis et al, 2007).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations